Determination of Some Selected Thermal Properties of Pumpkin Seeds (Cucurbita pepo) - M.O. Sunmonu; M.M. Odewole; O.A. Adeyinka; M.S. Sanusi; S.O. Musa (Journal of Applied Sciences and Environmental Management, 2021)
In this study, some selected thermal properties (specific heat, thermal conductivity and thermal diffusivity) in the moisture content range of 5.0-5.6% or green and 4.80 – 5.20% for white varieties of pumpkin seeds were determined. The specific heat was measured using mixture method while the thermal conductivity was measured by transient technique using the heat line source. The green pumpkin seed has average moisture content of 5.2% higher than moisture content of white pumpkin seed of average 4.8%. The average specific heat values of green pumpkin seed are 6.171kJ/kgK and white pumpkin seed 4.327kJ/kgK. The thermal conductivity values for white pumpkin seed ranged from 0.074 to 0.288 W/m°C while that for green pumpkin seed ranged from 0.079 to 0.433 W/m°C. The thermal diffusivity values for green pumpkin ranged from 0.0011 to 0.06 m2/s while that for white pumpkin seed ranged from 0.01 to 0.06 m2/s. It was concluded that the higher the moisture content (5.2%) the higher the value of specific heat of seed (6.171kJ/kgK). It can also be concluded that the thermal conductivity (0.079 to 0.433 W/m°C) value is higher with high moisture content (5.2%).